Legal terms in translation of regulation number 40 year 2007 regarding limited liability company in Indonesia - Suryasa, Wayan; Wirawan, I Gede Nika; Thoms, Steven L.; Bonviglio, Tom (Linguistics and Culture Review, 2021)
This research focused on the language being used in Regulation Number 40 year 2007 regarding limited liability company in Indonesia and the data is taken from Regulation Number 40 year 2007 regarding limited liability company in Indonesia that is collected randomly so the technique that will be used in this research is the sampling technique, because the data was chosen randomly and the method that will be used to analyze the data is descriptive method because the data will be described descriptively. It will describe the reason why the translator use that kind of equivalence to translate Indonesian into the English language.